2017
DOI: 10.1088/1367-2630/aa5fdd
|View full text |Cite
|
Sign up to set email alerts
|

Indirect methods to control population distribution in a large spin system

Abstract: We demonstrate how a large spin system ( = S 7 2) with the ground and first excited state separated by a seven-photon transition exhibits nonequilibrium thermodynamic properties and how the population distribution may be manipulated using coupling between energy levels. The first method involves non-adiabatic passage through an avoided level crossing controlled with an external DC magnetic field and the resulting Landau-Zener transition. The second method is based on external cavity pumping to a higher energy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…However, sometimes, only the dynamics of two close levels is relevant. We find this in the work of (Zhao et al, 2017) on a large-spin system, S = 7/2. The authors observed the nonadiabatic dynamics around one of the avoided-level crossings controlled with an external magnetic field in a Gd 3+ impurity ion ensemble, which makes a qubit system with "a virtually unlimited relaxation time".…”
Section: Some Experimental Observationsmentioning
confidence: 51%
“…However, sometimes, only the dynamics of two close levels is relevant. We find this in the work of (Zhao et al, 2017) on a large-spin system, S = 7/2. The authors observed the nonadiabatic dynamics around one of the avoided-level crossings controlled with an external magnetic field in a Gd 3+ impurity ion ensemble, which makes a qubit system with "a virtually unlimited relaxation time".…”
Section: Some Experimental Observationsmentioning
confidence: 51%